BASIC ASPECTS OF THE POLITICAL IDEOLOGY OF THE RELIGIOUS MOVEMENT „NEW GENERATION” - Kretalovs, Deniss (Via Latgalica, 2009)
The subject of the article – the religious organization “New Generation” – is discussed as a new religious movement, and in the aspect of sociology of religion is to be typologically interpreted as a Christian neo-charismatic evangelical movement having formed as a result of cleavage. Attention is focused on the ways of political collaboration of the movement “New Generation” and the fundamental aspects of its political ideology. The choice of the study subject is grounded on the lengthy and active activity of the group in the territory of Latvia, its topicality, popularity and dynamic growth in the material as well as in the social and political aspects. It is proved by several indicators of social attention and identification – the number of publications in press, intensity of thematic discussions and forums on the Internet, publicity measures, TV broadcasts, political and public activities. The aim of the paper is to identify the main aspects of the political ideology of the religious organization “New Generation” by analyzing the available sources. In order to clear up these aspects, it is necessary to view the courses of activity of the religious organization and its activities in the spheres of civil, public and political participation. As the reference objects, mass media materials have been used as well as periodicals featuring the discourse of the organization (interviews with the organization leaders). As the primary source, the book New World Order by Alexey Ledyaev, the founder and main leader of „New Generation”, has been used in which he voices the main postulates of his revelation as well as the political guidelines for the future development of the system of administration of the world and of Latvia. The book of A. Ledyaev is to be judged as the quintessence of the political ideology of „New Generation” following which the social life in the congregation of this movement has been formed and ensured and which determines the degree of political participation and content of the movement adherents. The following hypothesis is brought forward in the study – the elements and aspects forming the political ideology and the system of world-outlook and values of the religious movement “New Generation” clearly indicate a representation of the ideology of the Christian reconstructionism and its adaptation to the context and political situation of Latvia. Factors like the social agents involved in the formation of communication networks, the rhetoric of expression used in the construction of the space for discourse, the content of ideas reflected in the narratives applied in the context of the organization, models of development planning of the strategic policy and political slogans allow identification of “New Generation” as a religious movement oriented to Christian fundamentalism, which construct its political ideology using the political technologies and action models of the rightist Christians. The political ideology realized by the organization contains features of Christian reconstructionism – political programmes and strategies. On this score, „New Generation” belongs to those Christian fundamentalist organizations that practise a radical and clearly targeted policy.